2014
DOI: 10.1063/1.4875280
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the translational and rotational degrees of freedom on the hydration of simple solutes

Abstract: Molecular dynamics simulations with separate thermostats for rotational and translational motion were used to study the effect of these degrees of freedom on the structure of water around model solutes. To describe water molecules we used the SPC/E model. The simplest solute studied here, the hydrophobe, was represented as a Lennard-Jones particle. Since direct interaction between the hydrophobe and water molecules has no angular dependence the influence of the increase of the rotational temperature on the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…A simple spherical cut-off with a distance 9 Å was used for Lennard-Jones, as well as, for electrostatic interactions. 15 We have verified, that results did not change upon an increase of the cut-off distance.…”
Section: Model and Simulation Detailssupporting
confidence: 59%
See 4 more Smart Citations
“…A simple spherical cut-off with a distance 9 Å was used for Lennard-Jones, as well as, for electrostatic interactions. 15 We have verified, that results did not change upon an increase of the cut-off distance.…”
Section: Model and Simulation Detailssupporting
confidence: 59%
“…Our study also indicated that charge distribution on a solvent molecule could be important. This prompted us to explore to what degree the results obtained in references 14,15 depend on the chosen model of water. The question we wish to answer here is the following: can we expect the same trends as obtained for SPC/E also for other water models, or the results are model-dependent?…”
Section: Mohori~ Et Almentioning
confidence: 99%
See 3 more Smart Citations